The washback of EPLIS on teachers’ perceptions and actions: Implications for reviewing ICAO language policy in Brazil - Souza, Paula Ribeiro e (The ESPecialist, 2020)
This study investigated the washback effect of the Aeronautical English Language Proficiency Exam for the Brazilian Airspace Control System(EPLIS) on teachers’ perceptions and actions in an Air Traffic Control Initial Training Program. EPLIS has been administered to Brazilian in-service air traffic controllers and aeronautical station operators every year since 2007, in compliance with the International Civil Aviation Organization (ICAO) language proficiency requirements, published in 2003. These requirements set that all professionals involved in international flight operations shall demonstrate a minimum level of proficiency in the English language. In 2014, Brazilian air traffic control authorities decided to extend EPLIS application to pre-service air traffic controllers to supposedly improve learners’ proficiency in the training program. However, the consequences of this decision, whether intended or unintended, positive or negative, had not been appraised yet. Quantitative and qualitative data were collected through questionnaires, interviews and class observations. The results showed that the decision to introduce EPLIS in that educational context actually increased its impact. However, some teachers’ deficiencies in understanding the exam and its demands, along with an underrepresentation of air traffic control tasks in the test, compromised to some extent the intended effects and need to be handled so that ICAO language policy in Brazil can be entirely implemented.